Legal Framework for Regulating the Protection of the Rights of Older People: The Case of Kazakhstan - ADYLGAZY, Serikhan; KOZHABEK, Kanat; OMIRALI, Zhazira; TELEUYEV, Galym; DARHANBAYEVA, Ainur (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020, 2020)
The rapid aging of the population and the constant increase in life expectancy throughout the world is one of the greatest socio-economic and political transformations of our time. This article discusses the preparation of an integrated system to address the challenges of protecting the rights of older people. Also, based on the study of scientific works of foreign and domestic scientists on protecting the rights of older people at the international level and taking into account international standards and the implementation of international human rights treaties, analysis of the compliance of national legislation with international standards, an in-depth analysis of the legal powers of state bodies and other organizations of Kazakhstan related to protecting the rights of senior citizens. Insufficient attention in the field of domestic science is paid to the protection of the rights of the elderly. In addition, there are no state programs aimed at improving the protection of the rights of the elderly or addressing the problems of an aging population, and no relevant measures have been taken. The experience of foreign countries in the field of protecting the rights of elderly people is diverse, using it to improve the mechanism of legal regulation and the sphere of social services of Kazakhstan, we propose to put in place good aspects. However, taking into account the differences associated with legal and economic conditions, it is very important to implement in accordance with the legal system of the country.